2022
DOI: 10.1080/21645515.2022.2082205
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden of pneumococcal disease in children in Liguria, Italy

Abstract: Vaccinations against Streptococcus pneumoniae are included in infant immunization programs globally. However, a substantial burden due to pneumococcal disease (PD) remains. This study aimed to estimate the cost of emergency department (ED) visits and hospitalizations associated with invasive pneumococcal disease, all-cause pneumonia, and acute otitis media in children <15 years of age in the Liguria region of Italy between 2012 and 2018. The retrospective cohort study used data from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Several years have passed since Guest´s publication [ 53 ], and more recent studies assessing the direct cost per pneumonia episode in children in England are lacking. In a recent Italian study, Amicizia D., et al reported the median cost per ED visit or hospitalisation from 2012–2018 for PP (€3,323), and ACP (€1,850) [ 54 ], corresponding to £2,915 and £1,623 based on 2019 average exchange rate [ 50 ]. This contrasts with our study, where we found higher inpatient costs per episode in ACP compared to PP from 2003–2019, £3,549 (95% CI 3,405–3,693) for ACP versus £1,498 (95% CI 1,153–1,843) for PP.…”
Section: Discussionmentioning
confidence: 99%
“…Several years have passed since Guest´s publication [ 53 ], and more recent studies assessing the direct cost per pneumonia episode in children in England are lacking. In a recent Italian study, Amicizia D., et al reported the median cost per ED visit or hospitalisation from 2012–2018 for PP (€3,323), and ACP (€1,850) [ 54 ], corresponding to £2,915 and £1,623 based on 2019 average exchange rate [ 50 ]. This contrasts with our study, where we found higher inpatient costs per episode in ACP compared to PP from 2003–2019, £3,549 (95% CI 3,405–3,693) for ACP versus £1,498 (95% CI 1,153–1,843) for PP.…”
Section: Discussionmentioning
confidence: 99%
“…Average cost per episode was reported for pneumonia and IPD as €345 and €4,206, respectively. Similarly, a study within the Liguria region of Italy reported an increase in the number and cost of emergency department visits and hospitalizations associated with IPD, ACP and AOM in children aged < 15 years between 2012–2018, while costs associated with PP decreased [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond Germany, Shiri et al recently reviewed the annual HCRU spend on PD including IPD, pneumonia and AOM from 2010 to 2018 in high-income countries and showed an increase in cost and resources used (including both out-and inpatient care) [9]. In addition, a study conducted in the Veneto region of Italy from 2010-2017 in children < 15 years old [39], showed that IPD burden did [40].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a growing body of literature has focused on the emergence of residual burden, as serotypes of S . Pneumoniae not covered by available PCVs continue to circulate in the pediatric population [ 14 18 ]. As a consequence, higher-valent vaccines have been introduced in immunization programs, such as PCV10 (with additional serotypes 1, 5, and 7F) and PCV13 (with additional serotypes 3, 6A, and 19A) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ongoing changes in etiology and emergence of non-vaccine serotypes are a reason for growing concern in the medical community around antibiotic-resistant bacteria as a major cause of treatment failure in pediatric patients with AOM [12,13]. Furthermore, a growing body of literature has focused on the emergence of residual burden, as serotypes of S. Pneumoniae not covered by available PCVs continue to circulate in the pediatric population [14][15][16][17][18]. As a consequence, higher-valent vaccines have been introduced in immunization programs, such as PCV10 (with additional serotypes 1, 5, and 7F) and PCV13 (with additional serotypes 3, 6A, and 19A) [5].…”
Section: Introductionmentioning
confidence: 99%